Geospatial Approach to Solving Traffic Congestion Problems In Mushin Local Government Area of Lagos State - Leonard Michael Onyinyechi Aminigbo (International Journal of Information Systems and Informatics, 2022)
The variation in road conditions in relation to traffic congestion overtime enhances the need for proper development of a geospatial platform by comprehensively building and relating the attributes information of the entire road network with respect to various road segments. This is better executed through the concept of dynamic road segmentation. The aim of this study is to carry out geospatial data structure of dynamic road segmentation in Mushin local government area of Lagos State showing the road segment (spatial data) and its topological information.The selected roads within Mushin Local Government were extracted from a street map of Mushin Local Government Area gotten from the office of the Surveyor General of Lagos state. The selected roads were digitized to obtain the spatial information required for the road segmentation. The road vectorization or digitization was carried out in ArcGIS 10.2 software. It was created as a separate shapefile and added as a layer within the GIS environment.The information acquired from the field survey describing the road network as well as the segments i.e. the attribute information, formed a database developed in a GIS platform using ArcGIS 10.2 software. This relational database contains information such as name of road, segment ID, nature of roads, nature of segments, presence of pot holes, presence of crime scenes, presence of congestion, causes of congestion, local inhabitants of segment, length of segments, adjoining land use (to the left and right), mode of transportation along the segment, the traffic condition of the roads and the number of lanes of the road.These large amount of attribute information for all the segment were geospatially referenced with respect to the positions of all the segments and this is the basis of every GIS operation; providing an environment for relating the spatial locations of features with the attribute information describing the spatial feature (which in this case the roads and the road segments represents the spatial feature)Spatial query by attribute as well as location can easily be carried out to select road segments of interest based on predefined criteria using a specific Structural Query Language (SQL) within the GIS environment.Dynamic road segmentation provides a platform for planning and controlling changes on road network. Since the roads are broken down into segments, temporal changes of the road structure as well as the traffic conditions of the roads can be analysed and suitable decisions as well as policies for proper road maintenance can easily be taken and the policies implemented with respect to the segmentation of the roads. It also aids the security organization implementing platform within a GIS environment to monitor the crime scenes with respect to affected segment and would aid in the deployment of security agents at the appropriate locations in case of emergency.In the control of traffic, dynamic road segmentation aid in deciding the alternative conditions to follow since the entire road network have being spatially segmented and the conditions of all the segments built into the GIS database.